Challenges in Utilizing Information and Communication Technology for Teaching Basic Science and Technology in Secondary Schools in Rivers State - Nwiku, Bethel Barinaadaa; Momta, Philip Nukebabari (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2024)
This study examined the challenges in utilizing information and communication technology in teaching Basic Science and Technology in Secondary Schools in Rivers State. The study adopted a descriptive survey design. The population of the study comprises 2122 students and 35 Basic Science and Technology teachers. A sample of 794 respondents (759 students and 35 Basic Science and Technology teachers) were sampled for the study. Four research questions were answered while four hypotheses were tested at 0.05 level of significance. The instrument used for data collection was a structured questionnaire which was validated by three experts in the field of study. A reliability coefficient of 0.85 was obtained through Pearson Product Moment Correlation ( PPMC). The data collected was analyzed using mean and standard deviation, while the z-test for testing hypotheses. It was found that inadequate provision of ICT facilities, poor funding of schools, and inadequate supply of electricity were some of the challenges in the use of ICT in schools in Rivers State. Based on the findings, it was recommended among others that sufficient electric power be supplied to schools in the state, teachers should be motivated to use modern technology in the office as well as in the classroom through frequent workshops, conferences and seminars.